Chanteuse pop en milieu indé : entretien avec La Féline - Barbara Lebrun (Transposition, 2024)
The French singer-songwriter La Féline, who has been recording music since 2011, discusses her career by evoking her musical influences, her perception of gender biases in the music industry, the tension between mainstream and indie pop, the role played by her body and maternity, and finally how her music practice is influenced by and sometimes at odds with her job as a teacher and academic.